2009
DOI: 10.1007/s00198-009-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene ameliorates detrimental enzymatic and nonenzymatic collagen cross-links and bone strength in rabbits with hyperhomocysteinemia

Abstract: These results demonstrate that hyperhomocysteinemia reduced bone strength via a reduction of enzymatic cross-links and an increase of nonenzymatic cross-links. RLX may ameliorate hyperhomocysteinemia-induced detrimental cross-linking in rabbits with OVX and may improve bone strength via the amelioration of collagen cross-links.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 59 publications
2
65
0
1
Order By: Relevance
“…Li et al previously showed that plasma Hcy levels were significantly increased in patients with T2DM than those in non-diabetes subjects, and that higher plasma Hcy levels were associated with the incidence of vertebral fractures and hip fractures in patients with T2DM [33]. Although the mechanism underlying Hcy-induced bone fragility in DM is still unclear, several studies about the effects of Hcy on osteoblast function and collagen cross-links were reported [5,34]. Diet-induced hyperhomocysteinemia decreased bone quality in vivo [34], and Hcy directly affected osteoblast lineage cells such as bone marrow stromal cells and osteoblasts.…”
Section: Homocysteinementioning
confidence: 99%
See 1 more Smart Citation
“…Li et al previously showed that plasma Hcy levels were significantly increased in patients with T2DM than those in non-diabetes subjects, and that higher plasma Hcy levels were associated with the incidence of vertebral fractures and hip fractures in patients with T2DM [33]. Although the mechanism underlying Hcy-induced bone fragility in DM is still unclear, several studies about the effects of Hcy on osteoblast function and collagen cross-links were reported [5,34]. Diet-induced hyperhomocysteinemia decreased bone quality in vivo [34], and Hcy directly affected osteoblast lineage cells such as bone marrow stromal cells and osteoblasts.…”
Section: Homocysteinementioning
confidence: 99%
“…Although the mechanism underlying Hcy-induced bone fragility in DM is still unclear, several studies about the effects of Hcy on osteoblast function and collagen cross-links were reported [5,34]. Diet-induced hyperhomocysteinemia decreased bone quality in vivo [34], and Hcy directly affected osteoblast lineage cells such as bone marrow stromal cells and osteoblasts. We recently showed that Hcy induced the apoptosis of osteoblastic cells by increasing oxidative stress [5].…”
Section: Homocysteinementioning
confidence: 99%
“…Enzymatic cross-link formation has positive effects on bone mechanical properties within a beneficial range without brittleness [9,[15][16][17]. In contrast to the positive effects bestowed by enzymatic cross-links, AGE cross-links result in brittle collagen fibers, thereby leading to microdamage and bone fragility [18][19][20][21][22]. AGE cross-links are formed by oxidation or glycation reactions in a time-dependent manner, which is regulated by tissue turnover rate [21], the degree of oxidative stress [20,23], or glycation level [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al ранее сообщили, что уровни Hcy плазмы были достоверно выше у пациен-тов с СД2 по сравнению с пациентами, не страдающими диабетом, и что более высокие уровни Hcy были связаны с распространенностью переломов позвонков и бедра у пациентов с СД2 [19]. Диет-индуцированная гипергомо-цистеинемия снижает качество костной ткани in vivo [20], и Hcy непосредственно поражает клеточные линии осте-областов, такие как стромальные клетки костного мозга и остеобласты. Hcy индуцирует апоптоз остеобластов путем увеличения окислительного стресса [21].…”
Section: гомоцистеинunclassified